2016
DOI: 10.1111/rssb.12216
|View full text |Cite
|
Sign up to set email alerts
|

Concordance-Assisted Learning for Estimating Optimal Individualized Treatment Regimes

Abstract: In this article, we propose a new concordance-assisted learning for estimating optimal individualized treatment regimes. We first introduce a type of concordance function for prescribing treatment and propose a robust rank regression method for estimating the concordance function. We then find treatment regimes, up to a threshold, to maximize the concordance function, named prescriptive index. Finally, within the class of treatment regimes that maximize the concordance function, we find the optimal threshold t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 33 publications
4
76
0
Order By: Relevance
“…where Q is a strictly monotone increasing function with Q.0/ = 0. The parameters β g in each group can be consistently estimated by using the concordance-assisted learning method of Fan et al (2017). The properties of the corresponding maximin projection estimator warrant further investigation.…”
Section: Extensionsmentioning
confidence: 99%
“…where Q is a strictly monotone increasing function with Q.0/ = 0. The parameters β g in each group can be consistently estimated by using the concordance-assisted learning method of Fan et al (2017). The properties of the corresponding maximin projection estimator warrant further investigation.…”
Section: Extensionsmentioning
confidence: 99%
“…If the whole problem is offline, many methods have been proposed to solve it (e.g. Murphy, 2003;Zhao et al, 2012;Zhang et al, 2012Zhang et al, , 2013Fan et al, 2017). But when learning decision rules online, we are often faced with the classic dilemma between exploration and exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…Take the AIDS Clinical Trials Group Protocol 175 (ACTG175) study as an example. Many works in the literature have found that the age variable has significant qualitative interaction with the treatment (Lu, Zhang and Zeng, 2013; Fan et al, 2017). It is therefore of great importance to explore the CQTE of a new variable or a set of new variables given the age variable.…”
Section: Introductionmentioning
confidence: 99%